Extended Spectrum Beta-Lactamase Producing Gram Negative Pathogens in Urine Samples of Patients Visiting B.P. Koirala Memorial Cancer Hospital, Bharatpur, Nepal (Tribhuvan University Journal of Microbiology, 2025)
Objectives: To isolate and identify extended spectrum beta-lactamases producing Gram negative bacteria in urine samples of patient visiting B.P. Koirala Memorial Cancer Hospital, Chitwan, Nepal.Methods: Urine samples were processed to isolate and identify Gram negative bacteria by different biochemical tests (Gram stain, catalase test, oxidase test, indole test, MR test, VP test, citrate utilization test, TSIA test), antimicrobial susceptibility test was done as recommended by Clinical Laboratory Standard Institute (CLSI) and production of ESBL was determined by combination disk diffusion method.Results: Out of total 142 samples, prevalance of UTI in cancer and cancer suspected patients was found to be 24.64%. Of the total Gam negative isolates, the most predominant organism was found to be E. coli 63% followed by Klebsiella 26% and others 11.11%. Among 27 Gram negative isolates, MDR was found to be 81.48%. The prevalence of ESBL producers among the total Gram negative isolates was 11.11%. The higher rate of growth was seen in age group of 60- 70 (29.62%). Higher prevalence of bacterial growth was observed in male. Polymyxin B, Gentamycin and Nitrofurantoin were the most effective antibiotics towards Gram negative bacteria.Conclusion: The prevalence of MDR and ESBL among Gram negative uropathogens isolated from cancer and cancer related patients are quite high. Therefore, it is essential to have a regular monitoring of ESBL producing clinical isolates in laboratory practice.